Prevalence and Pattern of Ocular morbidity amongst school going children in rural and urban areas of Aligarh - Siddiqui, Ziya; Singh, Neetu; Khan, Adeeb Alam; Abedi, Ali Jafar; Siddiqui, Atika Javed; Zubair, Mohd Yasir (Indian Journal of Community Health, 2023)
Introduction: Many ocular diseases have their origin in early childhood and if the morbidity goes unnoticed it may adversely affect the child’s school performance and may also cause severe ocular disability in the later part of life. An early recognition and intervention leads to lifelong impact. Objective: To study the prevalence and pattern of various ocular morbidities in school going children of urban and rural areas of Aligarh. Methods: This was a cross-sectional study carried out from October 2017 to July 2019 in 10 schools in Aligarh, a district in North Western UP. Schools from urban and rural areas were listed and 5 urban and 5 rural schools were selected by lottery method. Results: Of the total 9982 students enrolled in study, 5742 children were from urban schools, and 4240 children were from rural schools. A total 2189 students were found to be suffering from various ocular morbidities, yielding an overall prevalence of ocular morbidity of 21.93%. The prevalence in urban and rural schools was 22.41% and 21.27% respectively (P=.286). Refractive error was found to be the most common ocular morbidity followed by Vitamin A Deficiency. Conclusion: Refractive errors and Vitamin A deficiency were the most common ocular disorders identified which are preventable and treatable causes of childhood blindness. These conditions can be easily identified by regular eye screening programs and promptly corrected. Awareness among school teachers should also be improved and they should play an active role in identifying the ocular problems and referring them for timely management.